Reintegration into school, kindergarten and work in families of childhood cancer survivors after a family-oriented rehabilitation program - Inhestern, Laura; Nasse, Mona L.; Krauth, Konstantin A.; Kandels, Daniela; Rutkowski, Stefan; Escherich, Gabriele; Bergelt, Corinna (Frontiers in Pediatrics, 2024)
Objective: To describe the situation of childhood cancer survivors and their parents before and one year after a family-oriented rehabilitation program (FOR) and to identify factors influencing reintegration.Methods: We included parents of children diagnosed with leukemia or central nervous system tumor. We assessed parental functioning using the functioning subscale of the Ulm Quality of Life Inventory for Parents (ULQIE) and children's school/kindergarten related quality of life (parental assessment, subscale KINDL-R). Descriptive analyses, group comparisons and multiple regression analyses on data of 285 parents of 174 children diagnosed with leukemia or central nervous system tumor.Results: Parents reported changes in their work situation (e.g. reduction of working hours) due to their child's diagnosis. Parental functioning increased significantly over time. Children's leukemia diagnosis and shorter time since the end of treatment were associated with higher functioning in parents one year after FOR. Parents reported difficulties in the child's work pace, concentration, stress resilience and empathy. The school/kindergarten-related quality of life (QoL) of the children was lower than in the general population. One year after FOR, most children reintegrated fully in school/kindergarten, partly with support (eg, integration assistant). No significant predictors for children's reintegration were identified.Discussion: Parents and children experience major changes in their work/school/kindergarten life. One year after FOR most parents reported a reintegration of their children, however the children's school/kindergarten-related QoL remained below average compared to norm values. Even after rehabilitation families of childhood cancer survivors might in addition to after-care benefit from psychosocial and practical support offers to support families with the reintegration into work/school/kindergarten.